(untitled) (Journal of Current and Advance Medical Research, 2020)
Background: Fistula in ano of complex variety has been a common surgical problem. Varieties of surgical procedures are encountered for management of this disease but recurrence is a notorious complication of this disease. Objective: The purpose of the present study was to assess outcomes of complex fistula in ano after fistulotomy with seton procedure. Methodology: This prospective study was performed in Dhaka Dental College, Dhaka, Bangladesh from January 2017 to December 2018 for a period of two years. Patients were included in this study. Data collected in data collection sheet regarding demographic data, types of operative procedures, post-operative complications and outcome of patients which were then analyzed. Result: Total 31 patients were included in this study. Age ranged from 20 to 60 years. Male was 28(90.32%) cases and female was in 3(9.68%) cases. High trans-sphincteric fistula were 28(90.32%) cases, extra-sphincteric fistula were 3(9.68%) cases. Fistulotomy with cutting seton by rubber bands were 12(38.71%) cases, fistulotomy with cutting seton by silk 19(61.29%) cases. Seton fell on its own 16(51.61%) cases, not fell 15(48.39%). Post-operative complications were incontinence of gas 5(16.13%) cases, incontinence of stool 1(3.23%) cases, recurrence 1(3.23%) cases. Conclusion: Outcomes of fistulotomy with cutting seton were satisfactory in most patients. Early recovery, low complication rate were encountered in treatment of complex fistula in ano by partial fistulotomy with cutting seton procedure. Journal of Current and Advance Medical Research 2020;7(1): 40-43